Insight into PPCP degradation by UV/NH2Cl and comparison with UV/NaClO: Kinetics, reaction mechanism, and DBP formation. (1st September 2020) - Li, Simiao; Ao, Xiuwei; Li, Chen; Lu, Zedong; Cao, Wenfeng; Wu, Fangfang; Liu, Shuming; Sun, Wenjun
Abstract: The UV/NH2 Cl process is an emerging advanced oxidation process (AOP) that is greatly effective in degrading pharmaceuticals and personal care products (PPCPs). However, detailed information regarding the process is lacking. The degradation of ibuprofen (IBP, an electron-withdrawing PPCP) and naproxen (NPX, an electron-donating PPCP) in UV/NH2 Cl and UV/NaClO processes was performed to investigate the applicability and security of the UV/NH2 Cl process and compare with those of UV/NaClO. UV/NH2 Cl was effective in degrading both IBP and NPX and the degradation followed pseudo-first order kinetics (kIBP  = 0.0037 cm 2 /mJ and kNPX  = 0.0044 cm 2 /mJ). This indicated the broad applicability of UV/NH2 Cl to different kinds of PPCPs. Ranges of values of UV intensity (0.3–1.0 mW/cm 2 ) and pH (6.0–8.0) showed little effect on the degradation of PPCPs by UV/NH2 Cl based on UV Dose but HCO3 − (2–8 mM), natural organic matter (NOM, 2–8 mg/L), and the natural water matrixes were inhibitory. Increasing the dosage of NH2 Cl from 0.15 mM to 0.75 mM, resulted in an even increase of kIBP ; however, kNPX increased slowly after 0.3 mM NH2 Cl. Mechanism experiments involving nitrobenzene showed that OH was the major radical involved in degrading IBP and NPX via UV/NH2 Cl. The electron spin resonance spectroscopy and kinetic modeling results also indicated the larger amount of OH and weaker reactive chlorine species (mainly ClO and ClO2 ) in UV/NH2 Cl compared with UV/NaClO. Compared to UV/NaClO in synthetic and natural water, UV/NH2 Cl was a more stable degrader with little pH- and substrate-dependence, while UV/NaClO preferred degrading the electron-donating PPCP and at low pH. The UV/NH2 Cl produced less halogenated disinfection byproducts (DBPs) (even nitrogenous DBPs) and was less cytotoxic theoretically than UV/NaClO based on the DBPs included in this study. Thus UV/NH2 Cl process may be an effective AOP for water treatment. Graphical abstract: Image 1 Highlights: OH is the predominant radical in the UV/NH2 Cl process. UV/NH2 Cl is a more stable degrader than UV/NaClO. UV/NH2 Cl is associated with a lower risk of disinfection byproducts than UV/NaClO.